Exploring the chemistry of epoxy amides for the synthesis of the 2"-epi-diazepanone core of liposidomycins and caprazamycins - Sarabia-García, Francisco Ramón; Vivar García, Carlos; García-Ruiz, Cristina; Martín Ortiz, Laura; Romero-Carrasco, Antonio (ACS, 2012)
New synthetic strategies have been explored for the synthesis of the structural core of liposidomycins and caprazamycins, an intriguing class of complex nucleoside-type antibiotics. This structural core is comprised of a cyclic diazepanone system linked to an uridyl fragment. The various synthetic approaches have in common that they originate from an epoxy amide derived from uridine, obtained via reaction of uridyl aldehyde 19 with an amide-stabilized sulfur ylide. Two different strategies were shown to be efficient in constructing the diazepanone ring system: (a) a reductive amination of an epoxy aldehyde with N methylamine with subsequent intramolecular oxirane ring opening and (b) a carbene insertion reaction of an acyclic diazoamine precursor.
Keywords: Antibióticos; aldehydes; amides; amines; ethers; organic polymers